The Digital Divide: Addressing Artificial Intelligence in Communication Education. (December 2020) - Luttrell, Regina; Wallace, Adrienne; McCollough, Christopher; Lee, Jiyoung
Artificial intelligence (AI) has gained both momentum and importance within society over the past several years. This article provides an opening for further discussion to the broader social and digital media research community and those interested in answering important questions related to these areas by leveraging a focused, productive approach. In supporting future educational endeavors within the communication classroom, and specifically to this topic, we propose five important considerations that will move the conversation forward. The considerations within this article are meant to engage scholars in intellectual conversation and to provide an initial foundation for the direction of communication education. They are not meant to be an exhaustive list, but rather initiate discussions within education and research addressing implications emerging technologies have had on our field and what could be incorporated into the media and communication curriculum to prepare educators and students alike.